Dinamika Komentar Negatif di Instagram: Studi Analisis Isi pada Kasus Cyberbullying terhadap Akun Instagram @abidzar73 - Jamil, Syakira Nasywa; Susanto, Tri; Budhiharti, Tri Widya (Jurnal Multidisiplin Dehasen (MUDE), 2025)
Popular social media platforms such as Instagram, X (formerly Twitter), Facebook, and TikTok serve as digital public spheres where people share opinions and engage in interactions that can generate both positive and negative social dynamics. One of the negative phenomena frequently found on social media is cyberbullying, a form of digital harassment conducted through comments, posts, or messages targeting an individual or group. This study focuses on the occurrence of cyberbullying on the Instagram account @abidzar73 during the period of January 14 - February 3, 2025, when Abidzar Al Ghifari was promoting the film A Business Proposal. The purpose of this research is to identify and describe the forms of cyberbullying comments posted by netizens in the comment section of the account. This study employs a descriptive qualitative method using content analysis as the primary approach. Data were collected through virtual observation of the relevant posts and analyzed systematically through data reduction, data presentation, and conclusion drawing. The findings reveal that the comments analyzed can be classified into four main categories based on Willard’s (2005) framework: flaming, harassment, denigration, and exclusion. Flaming is reflected in emotionally charged insults, harassment appears through repetitive derogatory comments, denigration is evident in the spread of false information and defamation, and exclusion takes the form of calls to boycott or socially ostracize the actor. Among these, exclusion emerged as the most dominant form. These results indicate that cyberbullying on social media is not merely a spontaneous emotional outburst but also represents a collective attempt to socially and professionally marginalize the victim..